Exploration of Renewable Energy Resources for Sustainable Development in Nigeria: A Study of the Federal Capital Territory - Akinwale, Yusuf Opeyemi; Ogundari, Ibikunle Olalekan (International Journal of Energy Economics and Policy, 2017)
This study examined renewable energy (RE) resources and their utilisation to achieve sustainable development (SD) in Nigeria. This was with the view of providing strategic assessment for sustainable energy development in the country consequent to the high level of environmental hazards which have trailed the path of many countries' economic growth and industrialisation. A survey method was adopted in the study whereby 300 copies of a single set of questions were distributed across the federal capital territory, Abuja. The results showed that most of the respondents perceived that the level of public awareness and publicity by the government on RE adoption is still relatively low. Majority of the respondents were not concern about reduction of greenhouse gas emissions as <20% were motivated to use RE due to environmental factors while more than 50% were motivated by economic factor. A strong political commitment of the government on RE and creation of enabling environment for the private sectors will go a long way to deliver social services such as health, education, clean water as well as employment creation which will foster the realisation of SD goals. Keywords: Sustainable Development, Renewable Energy, Sustainable Development Goals JEL Classifications: O13, O44, Q01, Q56